Circulating visfatin concentrations in patients with chronic obstructive pulmonary disease: systematic review and meta-analysis - Aboutaleb, Nahid; Moradi, Alireza; Mirshekari Jahangiri, Hamzeh; Aslani, Mohammad Reza (Frontiers in Medicine, 2025)
ObjectiveThe current study was designed with the aim of conducting a systematic review and meta-analysis to determine the circulating levels of visfatin in patients with chronic obstructive pulmonary disease (COPD) compared to healthy individuals.MethodsUntil March 2024, we searched the Web of Science, PubMed/Medline, and Scopus databases. The analysis included case–control studies assessing the association between circulating visfatin and COPD. The random effects model was utilized to analyse the results with the help of Standard Mean of Differences (SMD) and 95% confidence interval (CI). The heterogeneity of the data was assessed using Cochrane Q and I2 values.ResultsSeven studies were eligible to be included in the meta-analysis, with the COPD and healthy (control) groups having 265 and 244 subjects, respectively. The pooled results showed that although the circulating concentration of visfatin was lower in patients with COPD, no significant difference was observed (SMD: −0.48 mg/L; 95% CI: −1.67 to 0.70; p = 0.43). Subgroup analysis revealed that visfatin levels were significantly reduced in FEV1 less than 50% (p < 0.001) and in GOLD grade I-II (p < 0.05). Visfatin was shown to be significantly associated with IL-6 (p < 0.001) and TNF-α (p < 0.01) in the correlation meta-analysis. Meta-regression analysis revealed a significant correlation between the pooled SMD visfatin and pooled SMD age (p < 0.01), BMI (p < 0.001), FEV1 (p < 0.001), and IL-6 (p < 0.001).ConclusionThe findings showed an insignificant decline in visfatin level among COPD patients, but additional research is necessary due to the heterogeneity in study results.Systematic review registrationPROSPERO (CRD42023450851), https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023450851.